Biology and management of invasive quagga and zebra mussels in the western United States - Wong, Wai Hing; Gerstenberger, Shawn L., 1968- (CRC Press, 2015)
Biology and Management of Invasive Quagga and Zebra Mussels in the Western United States is a synthesis of the biology and management of invasive mussels from scientists and managers working on invasive quagga and zebra mussels in the western United States. Invasive dreissenid mussels have spread throughout southwestern United States at unprecedented speeds, and present a unique threat to native ecosystems. This book documents the efforts, both successful and unsuccessful, of individuals and agencies after dreissenid mussels invaded the West. Although the book is designed specifically for scie.
Keywords: Quagga mussel.; Zebra mussel.; Quagga mussel -- Control -- United States.; Quagga mussel -- Control -- West (U.S.); Zebra mussel -- Control -- United States.; Zebra mussel -- Control -- West (U.S.); Introduced organisms -- Control -- United States.; elektronické knihy; electronic books